2013
DOI: 10.1063/1.4818537
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of a single-stranded DNA with heterogeneous distribution of nucleobases in aqueous medium

Abstract: The DNA metabolic processes often involve single-stranded DNA (ss-DNA) molecules as important intermediates. In the absence of base complementarity, ss-DNAs are more flexible and interact strongly with water in aqueous media. Ss-DNA-water interactions are expected to control the conformational flexibility of the DNA strand, which in turn should influence the properties of the surrounding water molecules. We have performed room temperature molecular dynamics simulation of an aqueous solution containing the ss-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 48 publications
3
37
1
Order By: Relevance
“…Interestingly, no definite trend in the time evolutions of distance /interaction energy parameters is observed due to significant overcharging induced DNA chain reswelling at 0.3 and 1 M concentrations of Mg 2+ . The findings of this work are contrary to that of Chakraborty and coworkers [16] where it has been shown that an ss-DNA molecule exhibits reduced end-to-end distance, followed by higher lifetime of the stacked base pairs on increasing NaCl concentration up to 500 mM. These qualitatively different results in the case of ss-DNA in the presence of the similar concentrations of Na + and Mg 2+ ions, agree reasonably well with the experimental findings by Pollack et al that almost 20-40 times lower ionic strength of MgCl 2 than that of NaCl is sufficient to achieve the same chain compaction of ss-DNA and ss-RNA [55].…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Interestingly, no definite trend in the time evolutions of distance /interaction energy parameters is observed due to significant overcharging induced DNA chain reswelling at 0.3 and 1 M concentrations of Mg 2+ . The findings of this work are contrary to that of Chakraborty and coworkers [16] where it has been shown that an ss-DNA molecule exhibits reduced end-to-end distance, followed by higher lifetime of the stacked base pairs on increasing NaCl concentration up to 500 mM. These qualitatively different results in the case of ss-DNA in the presence of the similar concentrations of Na + and Mg 2+ ions, agree reasonably well with the experimental findings by Pollack et al that almost 20-40 times lower ionic strength of MgCl 2 than that of NaCl is sufficient to achieve the same chain compaction of ss-DNA and ss-RNA [55].…”
Section: Discussioncontrasting
confidence: 86%
“…For our study we take a single stranded Dickerson Drew dodecamer [23] with base sequence 5 0 -CGCGAATTCGCG-3 0 and all the simulations are carried out at 300 K. A trajectory of the DNA structure is obtained after a 50 ns simulation and the calculations of different parameters reveal the discrete patterns of structural collapse of ss-DNA when different counterion concentrations are involved under otherwise similar MD simulation conditions. MD simulations of the same ss-DNA at different Mg 2+ concentrations (0.01, 0.05, 0.1, 0.3 and 1 M) reveal a trend in structural changes, qualitatively different to that observed in the case of a monovalent species such as Na + [16]. A combined analysis of the data reported in this paper, may be helpful in comparing the patterns encountered in the structural collapse of the DNA at different concentrations of a divalent counterion such as Mg 2+ .…”
Section: Introductionmentioning
confidence: 49%
“…We use a B-form geometry for the model single-stranded oligonucleotide. The positive charge in the system is depicted as an hydronium ion formed by the binding of a water molecule to the departing proton, which is 2 Å apart from its original position on guanine-N1 to avoid unfavorable contacts [43,44], as is shown in point A of Fig. 6.…”
Section: Estimation Of the Electrostatic Contribution Of The Phosphatmentioning
confidence: 99%
“…In this particular arrangement, the central Na + counterion is surrounded by five non-hydrogen DNA atoms, three of which are from residue A6 (O4 0 , O1P and N3) and the remaining two are from residue C9 (O5 0 and O4 0 ). 24 Thus, it is clear that formation of a few such ion-induced inner-sphere complexes plays an important role in the formation of the folded configuration of ss-DNA. To analyze further how such Na + ion binding takes place, we have monitored the time evolutions of the distances (R) between the bound DNA atoms and the central Na + ion, as shown in Fig.…”
Section: Mechanism Of Na + Ion Induced Ss-dna Collapsementioning
confidence: 99%
“…[8][9][10][11] In the absence of cations, nucleic acids become relatively rigid macromolecules with longer persistence lengths. 24 In an important study, Murphy et al 25 reported single molecule fluorescence resonance energy transfer (FRET) measurements of a series of labeled oligodeoxythymidylates, (dT) N (10 r N r 70), over a wide range of NaCl concentrations. During folding both diffused and specifically bound ions are believed to play important roles.…”
mentioning
confidence: 99%